Intramolecular Arene C-H to C-P Functionalization Mediated by Ni(II) and Pd(II) - Suseno, Sandy (2013)
[Image: see text] A trisphosphine ligand with a triarylbenzene backbone was employed to support mono-nickel(II) and palladium(II) complexes. Two phosphine arms coordinated to the metal center, while the third phosphine was found to form a C-P bond with dearomatization of the central arene. Deprotonation effected the rearomatization of the central ring and metal reduction from M(II) to M(0). The overall conversion corresponds to a functionalization of an unactivated arene C-H bond to a C-P bond. This transformation represents a rare type of mechanism of C-H functionalization, facilitated by the interactions of the group 10 metal with the arene π-system. This conversion is reminiscent of and expands the scope of recently reported intramolecular rearrangements of biaryl phosphine ligands common in group 10 catalysis.